(untitled) ("Temas Sociais" Journal, 2025)
Homelessness is one of the most severe manifestations of social exclusion, reflecting multiple deprivations and the weakening of social and institutional ties. In Portugal, despite the efforts promoted by the National Strategy for the Integration of Homeless People, significant challenges remain in understanding the concrete needs of this population in local contexts. Based on a descriptive and quantitative approach, this study aimed to characterise the sociodemographic profile and perceived needs of People Experiencing Homelessness in Figueira da Foz, through the application of a sociodemographic questionnaire and an adapted version of the Needs Assessment Questionnaire. Data were collected from a sample of 27 individuals. The findings highlight housing, employment, and healthcare as central and recurring needs. Statistical analysis revealed a significant association between sleeping location and individuals’ perception of their ability to overcome homelessness. These results reinforce the need for integrated social responses that promote dignity, citizenship, and autonomy.